A Review on Novel Biochemical Mediator Triggered on Demand Drug Delivery System - Mithila Sawalwade; Anup Naha; Shubham Zende (Journal of Global Pharma Technology, 2020)
Unavailability of drug in appropriate amounts on apt time at the desired site of action can lead to further complications in the diseases which can turn into more deadly condition. Timely delivery of right amount of drug is very crucial in proper therapy, thereby avoiding the adverse effects of the drug. Feedback regulated closed loop delivery system can controllably deliver the drug on demand which means the release rates can be increased, decreased or totally stopped, as a response towards physiochemical response produced by the body. The system can be designed in such a way that the concentration of the drug released from the system is proportional to the degree of stimuli produced by the body. Various diseases and disorders progress by feedback loop mechanisms, owing to which biochemical signal triggered delivery of drug can be achieved in such conditions. The system is also advantageous in case of some drugs whose fluctuation in plasma concentrations is unenviable. In the current work, self-regulated drug delivery devices designed for various conditions like diabetes mellitus, hypercoagulation, cancer, microbial infections and opioid poisoning are reviewed. Various combinations of smart polymers are employed to design such devices that work by responding to the feedback produced by the body.